2001
DOI: 10.1097/00129492-200109000-00009
|View full text |Cite
|
Sign up to set email alerts
|

COCH5B2 Is a Target Antigen of Anti-Inner Ear Antibodies in Autoimmune Inner Ear Diseases

Abstract: These findings indicate that the 58-kDa target protein of antibodies in serum samples of patients with autoimmune inner ear diseases is the COCH5B2 protein, a molecule that is highly and specifically expressed in the cochlea and vestibule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Cochlin has also been implicated in autoimmune hearing loss in humans (Boulassel et al 2001;Baek et al 2006) and in experimental immune-mediated hearing loss in mice (Solares et al 2004). Similarly, CTL2 has been implicated in autoimmune hearing loss (Zeitoun et al 2005) and experimental antibodymediated hearing loss (Nair et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Cochlin has also been implicated in autoimmune hearing loss in humans (Boulassel et al 2001;Baek et al 2006) and in experimental immune-mediated hearing loss in mice (Solares et al 2004). Similarly, CTL2 has been implicated in autoimmune hearing loss (Zeitoun et al 2005) and experimental antibodymediated hearing loss (Nair et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our prior work has shown that immunization of SWXJ mice with the p131-150 peptide derived from mouse cochlin results in a significant loss of hearing that may be passively transferred into naive recipients with peptide-activated CD4 ϩ T cells (21,22). Cochlin antigenicity has also been shown in ASNHL since many patients have elevated serum levels of cochlin Abs (23).…”
Section: A Utoimmune Sensorineural Hearing Loss (Asnhl)mentioning
confidence: 99%
“…These early studies showed antibody recognition of inner ear tissues in patients suffering from hearing loss. Further characterization of antibodies from patients with SNHL using inner ear tissues from different mammalian species by Western blot analysis showed immune reactivity with several antigens of varied molecular weights [4,[10][11][12][13][14][15][16][17]. Several putative antigens have been identified as markers of AIED, but their role in the pathogenesis as well as relevance in disease-specific diagnosis remains undefined.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, antibodies against microbial pathogen and mammalian HSPs are present in healthy individuals as well as in various diseases, arguing against the significance of HSP antibodies in the serological diagnosis of AIED [18,19]. Other antigens of great potential include the cochlin protein, identified initially by Boulassel et al [12] as a candidate autoantigen for SNHL, myelin protein Po [15], choline transporter-like protein 2 [17] as well as b-tectorin [20,21]. The hypothesis of a pathogenic role for either cochlin or b-tectorin is supported by experimental induction of hearing loss following adoptive transfer of T cell lines specific for these proteins [21].…”
Section: Introductionmentioning
confidence: 99%